Video-Based Learning Media Development Training (Learning Videos and Video Assignment Recordings) Flipped Learning Model For Teachers at SMAN 2 Madapangga - Oya, Abas; Nurfidah, Nurfidah; Arwan, Arwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Learning methods and media are very influential for successful learning. Many teachers at SMAN 2 Madapangga do not apply technology to participate in learning. Lack of skills in the use of technological devices to support the teaching and learning process. Lack of utilization of adequate school facilities and infrastructure to support the learning process. One of the efforts offered is to conduct training on the development of flipped learning model video-based learning media for teachers of SMAN 2 Madapangga. Training on the development of learning media based on learning videos and training on the application of assignments based on video task recordings. The aim of the dedication is to increase the potential of teachers in developing learning media based on learning videos and training in the application of assignments based on video task recordings with a flipped learning model approach. This program is carried out in three stages. The preparation stage is conducting initial observations and designing various conceptual and administrative matters. Implementation is a learning model training (flipped learning) and video-based learning media. Finally, the evaluation stage is evaluating the implementation of the beginner community service program. The training and mentoring programs for teachers at SMAN 2 Madapangga ran smoothly and achieved the set objectives. This is indicated by an increase in teacher understanding of the learning model (Flipped Learning) by 55%, an increase in skills in making learning media with MC. Power Point, Canva and KineMaster applications by 66%, and an increase in the ability to develop learning media by 77%.